Analysis of the Implementation of the Independent Curriculum in Pioneer Schools to Foster Student Independence in History Subject for 10th Grade at SMAN 4 Palu - Charles Kapile; Nuraedah Nuraedah; Priyatna Prasetyawati (Dinasti Publisher, 2024)
The research problem is formulated as follows: